Standardization of frying as a pre-cooking method in canning roundscad (sardine style). - Mallen, Charito V. (College of Fisheries, University of the Philippines, 1977)
Sensory tastes were conducted in fried and fried then canned samples to establish the most suitable frying time-temperature, which serve as pre-cooking method in canning round scad. In addition, samples were analyzed for moisture content, protein content and pepsin digestibility tests to establish the standard range of moisture content in fish prior to canning and to see the effect on proteins. Increase in protein content is within the range of 54-61%. It was also found that canning rendered fish more digestible while frying produced a reverse effect in pepsin digestibility tests.